LITERACY PROBLEMS OF INFORMATION MANAGEMENT STUDY PROGRAMME GRADUATES - Macienė, Jurgita (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The article analyses literacy problems of Šiauliai State College Information Management Study Programme graduates. These graduates fall into the category of employees, for whom writing without errors is not a choice, but a necessity. The language study of the graduation papers showed that the students’ literacy is average: more than half (54%) of the papers were assessed as of typical or threshold level. Left spelling, punctuation, language errors, typographical errors have been found in the papers, the text is not always formated in accordance with the requirements of the scientific style. Key words: information management, study programme, learning outcomes of the programme, literacy, spelling, punctuation and language errors.